U-Pb zircon ages from the northern Austral basin and their correlation with the Early Cretaceous exhumation and volcanism of Patagonia - Ghiglione, Matias (2015)
The end of the Early Cretaceous sag stage along the Southern Patagonian Andes is indicated by the sudden appearance of shallow marine to deltaic sandstones on top of deep marine facies. We studied the detrital and volcanic zircon U-Pb geochronology from the coarse-grained deposits represented by the Río Belgrano and Río Tarde formations at the northern end of the Austral or Magallanes basin. The maximum depositional age of the basal green sandstones of Río Belgrano Formation is marked by a ~122. Ma age peak. The youngest single zircon of the overlaying lower Río Tarde Formation yields an age of 118±2. Ma, however the ~122. Ma age peak is equally present. The upper Río Tarde Formation yielded a 112±2. Ma U-Pb zircon age for a volcanic tuff. The ~122. Ma significant peak and 112±2. Ma tuff represent volcanic ash fall coeval with plutonic activity dated between 125 and 110. Ma in the North Patagonian Batholith. An abundant detrital Mesozoic population is present in both units, including a 189-170. Ma peak corresponding to the V1 Jurassic volcanic stage cropping out in the North Patagonian Massif. However, zircons of 153-157. Ma representing the age of Jurassic volcanism along the Patagonian basement domain to the west are scarce. Our data indicate a ~122. Ma age for the studied samples, during which the Southern Patagonian Andes received mixed basement and V1 Jurassic volcanic stage detritus. These combined sources are an outstanding characteristic of the North Patagonian and Deseado massifs, in agreement with the previously proposed Aptian uplift and exhumation of Patagonia.